THE GLOBAL EXPECTED HEALTH AND ENVIRONMENTAL EFFECTS OF CLIMATE CHANGE PHENOMENON - Elhassan Abdelslaam, Abdelellah Mohammed (Gezira Journal of Health Sciences, 2011)
A number of predictions have been made about the increase in temperature that is likely to occur over the next century or so as the result of the steady accumulation of greenhouse gases in the atmosphere. The scientists on the Intergovernmental Panel on Climate Change (IPCC) examined a number of scenarios and calculated that, the global mean temperature will increase by about 0.3 C per decade (with a range of 0.2-0.5 C per decade). This will lead to an increase in the global mean temperature of about 1 C above the present value by 2050 and 3 C  by 2100. These are realized rises in temperature, and they account for only about 60%- 80% of the final rise because the thermal inertia of the oceans acts as a buffer (Houghton, 1990). A number of feedback mechanisms can come into play, and these can either increase or reduce change.